Centralization or decentralization? A spatial analysis of archaeological sites in northern China during the 4.2 ka BP event - Zhang, Shengda; Zhang, David D. (Frontiers in Earth Science, 2023)
The phenomenon of centralization or decentralization has been widely observed in archaeological research. Studies are usually related to the evolution and dynamics of culture or civilization, but less pertinent to the temporal–spatial pattern and variation of human settlement, especially the insufficient applications of statistics and spatial analyses; also, their relationship with climate change is unclear. In this study, using the one-way analysis of variance (one-way ANOVA) and standard deviational ellipse (SDE) with its parameters and frequency histogram, with thousands (>4,000) of document-based data on archaeological sites (the indicator of human settlement), two pairs of successive cultural types, i.e., Majiayao–Qijia cultures and Longshan–Yueshi cultures in both ends of northern China were compared as cross-regional cases to uncover whether the locations of prehistoric settlements with ended or started ages were (de-) centralized under the impacts of climate cooling and aridification during the well-known “4.2 ka BP event” (4200–3900 BP). The results illustrate that the “inherited” sites become more decentralized. Such a pattern embodies human resilience (including adaptation and migration) for pursuing better living conditions under the circumstances of climatic and environmental deterioration over the mid–late Holocene cultural transition, which provides some implications for the response to contemporary climate change.